PENGARUH PEMBIAYAAN SYARIAH PADA BANK MUAMALAT DAN BANK BRI SYARIAH TERHADAP LIKUIDITAS - Retnowati, Candra; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence of murabahah finance, istishna, ijarah, mudharabah and musyarakah finances to the to the liquidity at Bank Muamalat Indonesia (BMI) and BRI Syariah Bank (in 2009-2014 periods). The method has been done by using desciptive qualitative which is meat to get the description how great the influence of murabahah, istishna, ijarah, mudharabah and musyarakah finances to the liquidity on the Bank Muamalat Indonesia (BMI) and BRI Syariah Bank. The data collection has been done by using secondary data which has been obtained from the quarterly financial statements which have been published by each syariah banks which have been selected as samples throuhg each banking website.It has been found from the result of the research which is based on the model feasibility (godness of fit test) that murabahah finance, istishna, ijarah, mudharabah, and musyarakah have significant influence to the liquidity with its significance value is 0.000. The significance test (t test) shows that there are 4 variabels which have positive and significant influence to the liqudity, i.e.: murabahah finance, istishna, mudharbah and musyarakah variables. Meanwhile, the remaining 1 variable is ijarah does not have any significant and negative influence to the liquidity of Bank Muamalat Indonesia (BMI) and BRI Syariah Bank. Keywords : Islamic Financing, Liquidity, Hypothesis Testing.